Strategies to improve the efficiency of mesenchymal stem cell transplantation for reversal of liver fibrosis - Hu, Chenxia; Zhao, Lingfei; Duan, Jinfeng; Li, Lanjuan (Journal of cellular and molecular medicine, 2019)
End‐stage liver fibrosis frequently progresses to portal vein thrombosis, formation of oesophageal varices, hepatic encephalopathy, ascites, hepatocellular carcinoma and liver failure. Mesenchymal stem cells (MSCs), when transplanted in vivo, migrate into fibrogenic livers and then differentiate into hepatocyte‐like cells or fuse with hepatocytes to protect liver function. Moreover, they can produce various growth factors and cytokines with anti‐inflammatory effects to reverse the fibrotic state of the liver. In addition, only a small number of MSCs migrate to the injured tissue after cell transplantation; consequently, multiple studies have investigated effective strategies to improve the survival rate and activity of MSCs for the treatment of liver fibrosis. In this review, we intend to arrange and analyse the current evidence related to MSC transplantation in liver fibrosis, to summarize the detailed mechanisms of MSC transplantation for the reversal of liver fibrosis and to discuss new strategies for this treatment. Finally, and most importantly, we will identify the current problems with MSC‐based therapies to repair liver fibrosis that must be addressed in order to develop safer and more effective routes for MSC transplantation. In this way, it will soon be possible to significantly improve the therapeutic effects of MSC transplantation for liver regeneration, as well as enhance the quality of life and prolong the survival time of patients with liver fibrosis.